Comparison of Acidity Test Method of Nickel Phosphate Silica Catalyst for Production Levulinic Acid from Glucose - Qodria Utami Putri; Hasanudin Hasanudin; Ady Mara (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2022)
The reaction of levulinic acid production from glucose has a reaction stage that requires a high temperature and high activation energy so that in this levulinic acid production reaction a catalyst is needed. The required catalyst must have a lewis acid site and a bronsted acid site so that the acidity of the catalyst is very influential for the successful production of levulonic acid. Silica nickel phosphate catalysts have lewis acid sites from Ni metal and bronsted acid sites from phosphoric and silica groups. The acidity of the catalyst was measured using the pyridine and ammonia adsorption method and the acidity center strength method using the TGA-DTA base adsorption-desorption. The adsorption of ammonia and pyridine uses the gravimetric method so that it can easily obtain the amount of total acidity of the catalyst and the acidity of the catalyst surface while the TGA-DTA method shows the acid strength of the actual catalyst, which is the real state of the catalyst when catalyzing a reaction and shows the catalyst's resistance to high temperatures. These two methods of measuring acidity have the same disadvantage that they cannot show and know the number of lewis acid sites and bronsted acid sites.